(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The role of state and public organizations, legal and public commissions is high in conducting important social, spiritual, educational and educational measures in preventing negative changes in adolescent behavior. State bodies are municipalities, law enforcement agencies, educational, youth, culture, Labor and social services and other types of bodies that play a specific role in implementing state policies in areas related to youth, in particular adolescents, raising their life positions. This process is a systematic activity and plans for programs and measures that have a progressive and constructive importance in the implementation of public policy in ensuring the interests of young people are carried out at the deadline.